Exploring the evolutionary characteristics between cultivated tea and its wild relatives using complete chloroplast genomes - Peng, Jiao (BMC Ecol Evol, 2021)
BACKGROUND: Cultivated tea is one of the most important economic and ecological trees distributed worldwide. Cultivated tea suffer from long-term targeted selection of traits and overexploitation of habitats by human beings, which may have changed its genetic structure. The chloroplast is an organelle with a conserved cyclic genomic structure, and it can help us better understand the evolutionary relationship of Camellia plants. RESULTS: We conducted comparative and evolutionary analyses on cultivated tea and wild tea, and we detected the evolutionary characteristics of cultivated tea. The chloroplast genome sizes of cultivated tea were slightly different, ranging from 157,025 to 157,100 bp. In addition, the cultivated species were more conserved than the wild species, in terms of the genome length, gene number, gene arrangement and GC content. However, comparing Camellia sinensis var. sinensis and Camellia sinensis var. assamica with their cultivars, the IR length variation was approximately 20 bp and 30 bp, respectively. The nucleotide diversity of 14 sequences in cultivated tea was higher than that in wild tea. Detailed analysis on the genomic variation and evolution of Camellia sinensis var. sinensis cultivars revealed 67 single nucleotide polymorphisms (SNPs), 46 insertions/deletions (indels), and 16 protein coding genes with nucleotide substitutions, while Camellia sinensis var. assamica cultivars revealed 4 indels. In cultivated tea, the most variable gene was ycf1. The largest number of nucleotide substitutions, five amino acids exhibited site-specific selection, and a 9 bp sequence insertion were found in the Camellia sinensis var. sinensis cultivars. In addition, phylogenetic relationship in the ycf1 tree suggested that the ycf1 gene has diverged in cultivated tea. Because C. sinensis var. sinensis and its cultivated species were not tightly clustered. CONCLUSIONS: The cultivated species were more conserved than the wild species in terms of architecture and linear sequence order. The variation of the chloroplast genome in cultivated tea was mainly manifested in the nucleotide polymorphisms and sequence insertions. These results provided evidence regarding the influence of human activities on tea. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12862-021-01800-1.